How, why and why not – the reflective practice of teaching staff at a Scottish university. Issue 5 (3rd September 2022) - Bray, Rob; Fotheringham, Heather
ABSTRACT: This two-stage study was conducted to examine the awareness of policy and underlying pedagogy as well as the use of reflective practice by teaching staff (faculty) within a Scottish university. In the first stage, teaching staff completed a questionnaire; of these 14 then took part in stage two, semi-structured interviews. Interview transcripts were subject to thematic analysis and three main themes emerged: (1) The methods and processes of reflection ('How'); (2) The personal and organisational drivers for employing reflective practices ('Why'); and (3) The barriers to reflection ('Why not'). Significant findings included the dominance of traditional (paper-based as opposed to computer mediated) reflective writing in teaching staff's own reflection, and the importance of both formal and informal group reflection in methods and process. Reasons for reflection focused on the importance of both organisational drivers such as professional standards and awarding bodies, and personal drivers such as personal growth, identity, and psychological wellbeing. Barriers to reflection included both the concrete such as insufficient time and lack of opportunities to share resources, as well as the attitudinal and cultural. Possible ways of tacking these barriers also emerged. Implications for organisational and individual practice are discussed.